2009
DOI: 10.1007/s12374-009-9023-0
|View full text |Cite
|
Sign up to set email alerts
|

Stable Plastid Transformation in Nicotiana benthamiana

Abstract: Plastids from Nicotiana benthamiana were transformed with the vector for dicistronic expression of two genes-aminoglycoside 3'-adenyltransferase (aadA) and green fluorescent protein (gfp)-in the plastids of Nicotiana tabacum. Transplastomic shoots exhibited green fluorescence under UV light. Transformation efficiencies were similar between species. Although the border sequence (trnI and trnA) for homologous recombination to transform the plastid genome of N. benthamiana was identical to that sequence of N. tab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 18 publications
1
17
0
1
Order By: Relevance
“…First, successful chloroplast transformation was reported in Chlamydomonas [12]. Then chloroplast transformation has been extended to an increasing number of dicotyledonous plants, including important plant bioreactor for pharmaceutical proteins: tobacco [7,[13][14][15]; the model plant species: Arabidopsis thaliana [16], petunia [17], and poplar tree [18]; species important in industrial economy: oilseed rape [19], Lesquerella fendleri [20], cotton [21], and sugar beet [22]; and edible crops: potato [23], tomato [24], carrot [25], soybean [26], lettuce [27,28], cauliflower [29], and cabbage [30]. Some preliminary studies have been made in chloroplast transformation of monocotyledonous species.…”
Section: Introductionmentioning
confidence: 99%
“…First, successful chloroplast transformation was reported in Chlamydomonas [12]. Then chloroplast transformation has been extended to an increasing number of dicotyledonous plants, including important plant bioreactor for pharmaceutical proteins: tobacco [7,[13][14][15]; the model plant species: Arabidopsis thaliana [16], petunia [17], and poplar tree [18]; species important in industrial economy: oilseed rape [19], Lesquerella fendleri [20], cotton [21], and sugar beet [22]; and edible crops: potato [23], tomato [24], carrot [25], soybean [26], lettuce [27,28], cauliflower [29], and cabbage [30]. Some preliminary studies have been made in chloroplast transformation of monocotyledonous species.…”
Section: Introductionmentioning
confidence: 99%
“…However, based on GFP protein accumulation in leaves, tubers and petals, it is clear that the relative performance of rrn and clpP regulatory sequences, and their potential applicability in plastid transformation approaches, vary with plastid types. In recent experiments in transplastomic N. benthamiana plants expressing the gfp gene under the control of the rrn promoter, decreasing transcript and protein expression levels were observed in leaves, petals and roots (Davarpanah et al 2009). The clpP 5 0 -UTR was previously used in combination with the rrn promoter to express the NPTII protein in tobacco leaves, but a mutant (chlorotic) phenotype was observed, even at low accumulation levels (Kuroda and Maliga 2002).…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, no apparent reductions in transformation frequencies were observed in tobacco and tomato using homologous or homeologous N. tabacum and S. nigrum ptDNA sequences in transformation vectors (Kavanagh et al 1999;Horváth et al 2000;Nugent et al 2005;Nugent et al 2006), or in transformations of N. benthamiana plastids with tobacco-derived vectors (Davarpanah et al 2009), indicating that species-specific vectors are not always necessary. In the tobacco and tomato studies, it was demonstrated that integration of the cloned homeologous ptDNA sequences in the host plastome occurred by multiple recombination events in a similar region of the inverted repeats (IRs), that in comparison with ''Single Copy'' regions of the plastid genome, generally show a higher gene order conservation and a lower sequence divergence (Maier et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations